Nursing law and ethics - Jahn Kassim, Puteri Nemie (International Law Book Services, 2012)
Recent changes in the provision of health care have contributed to the growing importance of nursing law and ethics. The role of nurses has transgressed into many litigated areas concerning issues in negligence, informed consent, confidentiality and euthanasia. The nursing legislations do not cater for many legal and ethical issues, which require a comprehensive set of law with considerable convergence between legal and ethical judgments. Technological advances in health care have also created challenges for the nursing profession. These challenges would require them to redress the imbalance by becoming more active in ethical decision-making and become a generalist and specialist, a communicator, a team collaborator, a caring presence as well as a vigilant professional. Educating nurses on the demands of law and high ethical standards would ensure greater accountability, knowledge and personal commitment in providing health care to individuals at every stage of their life. There is also an increased interest amongst the nursing profession to know about the legal principles applicable to their practice. In order to be responsible, the nursing profession should be made aware of the legal principles governing their profession. Ignorance of the law is by no means a defence for anyone. The increase in litigation as well as judicial and legislative intervention in most profession has made it essential for the nursing profession to be more knowledgeable in legal matters and anxious as to the extent of their accountability to their patients. Knowledge of and adherence to the law is an imperative professional responsibility.